2011
DOI: 10.1002/chem.201002389
|View full text |Cite
|
Sign up to set email alerts
|

Amine Exchange in Formamidines: An Experimental and Theoretical Study

Abstract: N-H-containing formamidines combine a reasonably strong association to carboxylic acids to form complexes of well-defined geometries with a simultaneous proton-induced electrophilicity enhancement that allows for the exchange of their amine portion. The N=C(H)-NH fragment, therefore, undergoes "imine-like" exchange with N-containing nucleophiles. Because of the prototropic equilibrium, the N=C(H)-NH fragment may behave as a "bisimine" centred on the same carbon, in which both N-containing fragments can be exch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 152 publications
0
11
0
Order By: Relevance
“…Thus DCBs are of significance at both the molecular and the materials level. The dynamic properties of DCBs are triggered by changes in various conditions, such as temperature, pH value, redox conditions, and light …”
Section: Methodsmentioning
confidence: 99%
“…Thus DCBs are of significance at both the molecular and the materials level. The dynamic properties of DCBs are triggered by changes in various conditions, such as temperature, pH value, redox conditions, and light …”
Section: Methodsmentioning
confidence: 99%
“…The reactivity of several types of amines towards formamidines was tested to explore which of them would exchange both ends of the group without changing the geometry, and do so preferably without breaking free of the carboxylate template (Scheme 17). 29 Various alkyl amines and aryl amines were tested (109-114). Arylamines (e.g.…”
Section: 214mentioning
confidence: 99%
“…Our observation is corroborated by computational studies by Petitjean and coworkers who showed that a carboxylate ion served as a proton shuttle in the mechanism proposed for the exchange of N,N 0 -diarylsubstituted formamidinium ions. 19 One of the key features of compounds with dynamic covalent bonds is their ability to undergo metathesis reactions. 34,[36][37][38][39] This type of DCR has been widely used in numerous fields including the synthesis of polymers as well as advanced molecular architectures and the exploration of complex chemical systems.…”
mentioning
confidence: 99%
“…18 A remarkable example of an amine-based DCR was reported in 2011 by Petitjean and coworkers who recognized the dynamic covalent nature of amidines. 19 In this first report, the authors focused on the exchange of aryl amines with N,N 0 -diarylformamidines and demonstrated that this DCR could be used for the carboxylate-templated assembly of macrocycles. 19 It occurred to us that amidines and their amidinium salts are widely used in coordination chemistry, 20 biomedical science, 21,22 advanced materials, 23,24 and supramolecular chemistry, 25,26 and therefore deserve a wider exploration from the perspective of DCvC.…”
mentioning
confidence: 99%